SPK: Analisis Algoritma Moora Pada Pembeliaan Televisi Sebagai Solusi Keluarga Bijak - Ilfi Rahmadani; Evi Mustiayu; Nina Agustiani; Debby F Saragih (Puslitbang Kopertip Indonesia, 2019)
The quality of a television is very important in purchasing, it is necessary to research that can help the community in purchasing television for wise kelurga.pada this research made a decision support system that implements Multi-Objective Optimization Method on the basis of Ratio Analysis (MOORA) with the method can provide the best alternative in determining the television as a wise family solution based on the existing criteria, As for some alternatives used are: Polytron, Samsung, Panasonic, LG, Thosibha, Pilips and some criteria such as: Model, Quality, Brand, Size and Price. The research data was obtained from the questionnaire / questionnaire based on the respondents of the community, in the use of MOORA method, the results of research in recommending the purchase of television as a wise family solution is an alternative A1 (politron) 0.1701 as 1st ranking, A5 alternative (Philips) 0.1652 as 2nd ranking and Alternative A2 (Toshiba) 0.0947 as 3rd ranking.